Anxiety from a Phylogenetic Perspective: Is there a Qualitative Difference between Human and Animal Anxiety?. (7th June 2007) - Belzung, Catherine; Philippot, Pierre
Abstract : A phylogenetic approach to anxiety is proposed. The different facets of human anxiety and their presence at different levels of the phylum are examined. All organisms, including unicellular such as protozoan, can display a specific reaction to danger. The mechanisms enabling the appraisal of harmful stimuli are fully present in insects. In higher invertebrates, fear is associated with a specific physiological response. In mammals, anxiety is accompanied by specific cognitive responses. The expression of emotions diversifies in higher vertebrates, only primates displaying facial expressions. Finally, autonoetic consciousness, a feature essential for human anxiety, appears only in great apes. This evolutive feature parallels the progress in the complexity of the logistic systems supporting it (e.g., the vegetative and central nervous systems). The ability to assess one's coping potential, the diversification of the anxiety responses, and autonoetic consciousness seem relevant markers in a phylogenetic perspective.